Pengaruh Online Customer Rating, Online Customer Review, dan Potongan Harga terhadap Minat Beli di TikTokShop (Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi) - Kevin Kevin; Dedek Kusnadi (ARZUSIN, 2025)
The advancement of digital technology has shifted consumer behavior from conventional shopping to online shopping, including through social commerce platforms such as TikTok Shop. However, understanding the key factors influencing purchase intention remains limited. This study aims to analyze the effects of online customer ratings, online customer reviews, and discounts on purchase intention among students of the Faculty of Islamic Economics and Business (FEBI) at UIN Sulthan Thaha Saifuddin Jambi. A quantitative approach with descriptive and verificative methods was employed. The sample consisted of 94 active students from the 2021–2022 cohorts who had purchased from TikTok Shop at least twice, selected using purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression, classical assumption tests, t-tests, F-tests, and the coefficient of determination (R²). The results indicate that online customer ratings do not significantly affect purchase intention, while online customer reviews and discounts exert a positive and significant influence. Simultaneously, the three variables significantly affect purchase intention, with an adjusted R² of 69.8%, indicating that variations in purchase intention are substantially explained by the independent variables. This study concludes that consumer reviews and discount strategies are the primary drivers of student purchase intention on TikTok Shop, with practical implications for online businesses to emphasize trust-building and price incentives in digital marketing strategies.